rgf Encodes a Novel Two-Component Signal Transduction System of Streptococcus agalactiae - Spellerberg, Barbara (American Society for Microbiology, 2002)
The adhesion of gram-positive bacteria to extracellular matrix (ECM) proteins is regarded as an important determinant of pathogenicity. A comparison of the adhesion of Streptococcus agalactiae strain O90R to different ECM proteins showed that the most pronounced binding could be observed for immobilized fibrinogen. To investigate the genetic determinants of S. agalactiae fibrinogen binding, a pGhost9:ISS1 mutant library was screened for mutants displaying reduced agglutination of fibrinogen-coated latex beads. A putative two-component signal transduction system was identified and designated rgfBDAC. It comprises genes encoding a putative response regulator of 218 amino acids and a putative histidine kinase of 426 amino acids. Comparison of the deduced proteins with the GenBank database revealed a significant similarity to quorum-sensing systems of gram-positive pathogens. Transcription analysis of the rgf locus showed that the encoding genes are located on one transcript. To further characterize the influence of the putative histidine kinase encoded in the rgf locus on the adhesion of S. agalactiae to immobilized fibrinogen, a targeted mutant of rgfC was generated. In comparison to the wild-type strain this mutant demonstrated altered fibrinogen binding capacities depending on bacterial cell density. Transcription analysis of secreted and surface-localized S. agalactiae proteins in the wild type and the rgfC mutant strain revealed that mRNA levels of the C5a peptidase gene scpB were increased in the mutant strain while the transcription of the secreted CAMP factor gene cfb was unaffected by this mutation. Based on these results, we hypothesize that rgf regulates the expression of bacterial cell surface components.